PENGARUH LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN INFORMASI SOSIAL PADA PERUSAHAAN MANUFAKTUR DI BEI - ., NOVRIANTO (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
The current information that has been required by the Government to each company's information on social responsibility or corporate social responsibility (CSR). Social responsibility is a concept that rganizations, in particular the company because it has a responsibility to consumers, employees, shareholders, communities and the environment in all aspects of the company's operations. Therefore, this research aims to analyze the factors affecting the disclosure of information on the social manufacturing company in Indonesia stock exchange (IDX) period 2008- 2010. A variable that is used is the disclosure of research information or CSR, social leverage, profitability, and the size of the company. This research uses the technique of purposive sampling that have criteria i.e. manufacturing company has to publish and publicize annual report 2008-2010 period in its entirety. The study used a sample of the 21 companies with manufacturing 2008-2010 period. Techniques of data analysis using regression analysis. The results of analysis demonstrate that leverage proven had a negative influence and is not significant to social information disclosure. In addition, profitability is proven to have a positive and significant influence to the disclosure of the information society. This means that the higher the value of the profitability of the company then the less social information disclosure. On the company size shows that have a positive influence and don't significantly to social information disclosure.